Interventions a life in war and peace - Annan, Kofi (The Penguin Press, 2012)
Receiving the Nobel Peace Prize in December 2001, United Nations Secretary-General Kofi Annan spoke to a world still reeling from the terrorist attacks of September 11. "Ladies and Gentlemen," proclaimed Annan, "we have entered the third millennium through a gate of fire. If today, after the horror of 11 September, we see better, and we see further-we will realize that humanity is indivisible. New threats make no distinction between races, nations, or regions." Yet within only a few years the world was more divided than ever-polarized by the American invasion of Iraq, the Arab-Israeli conflict, the escalating civil wars in Africa, and the rising influence of China. Interventions: A Life in War and Peace is the story of Annan's remarkable time at the center of the world stage. After forty years of service at the United Nations, Annan shares here his unique experiences during the terrorist attacks of September 11; the American invasions of Iraq and Afghanistan; the war between Israel, Hizbollah, and Lebanon; the brutal conflicts of Somalia, Rwanda, and Bosnia; and the geopolitical transformations following the end of the Cold War. With eloquence and unprecedented candor, Interventions finally reveals Annan's unique role and unparalleled perspective on decades of global politics.